Estimating strut forces for excavation support systems - Bernard, Hendrie. (2013)
Braced excavation has been widely used for basement and other infrastructure projects in Singapore. The supporting system is carried out using struts which are preloaded after the connection to the waler takes place. The struts are monitored regularly to check the deformation of the steel in order to prevent any failure in the supporting system. Several studies have been proposed in measuring the strut loads where the Peck's Apparent Pressure Diagram or APD is commonly used in design.